The aquatic communities inhabiting internodes of two sympatric bamboos in Argentinean subtropical forest - Campos, Raúl Ernesto (2013)
In order to determine if phytotelmata in sympatric bamboos of the genus Guadua might be colonized by different types of arthropods and contain communities of different complexities, the following objectives were formulated: (1) to analyze the structure and species richness of the aquatic macroinvertebrate communities, (2) to comparatively analyze co-occurrences; and (3) to identify the main predators. Field studies were conducted in a subtropical forest in Argentina, where 80 water-filled bamboo internodes of Guadua chacoensis (Rojas Acosta) Londoño and Peterson (Poales: Poaceae) and G. trinii (Nees) Nees and Rupr. were sampled. Morphological measurements indicated that G. chacoensis held more fluid than G. trinii. The communities differed between Guadua species, but many macroinvertebrate species used both bamboo species. The phytotelmata were mainly colonized by Diptera of the families Culicidae and Ceratopogonidae.